Impact of economic crisis on higher education in Malaysia - Hassan, Arif (International Institute of Educational Planning/UNESCO, 2001)
Malaysia has consistently demonstrated spectacular growth during the past four decades. The development policies followed by the country ensured growth with social justice: reducing the gap between rich and poor and building up human capital with high investment in the social and education sectors. Economic and social policies of the government were developed against the backdrop of political stability, high rate of employment, social peace, and high household savings. In order to infuse efficiency and increase productivity, economic policies of the country favoured privatization and reduction in public expenditure as a share of GDP.